2008
DOI: 10.1002/ejoc.200800250
|View full text |Cite
|
Sign up to set email alerts
|

Radical Carbodiazenylation – A Convenient and Effective Method to Achieve Carboamination of Non‐Activated Olefins

Abstract: The regioselective addition of aryl and aryldiazenyl substituents to olefinic substrates can be described as carbodiazenylation. In this report we present our final results relating to this unique type of radical functionalization reaction, which has now been developed into a convenient, versatile and highly effective synthetic method. Starting from an investigation into rate constants for the addition of aryl radicals to monosubstituted, non-activated olefins, this key step is shown to be both fast and select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 77 publications
0
31
0
1
Order By: Relevance
“…Based on these observations we concluded that the reaction most likely proceeds via direct capture of an sp 2 -hybridized carbon radical intermediate with TEMPO 18-21 (Scheme 1). The complete retention of the geometry of the isolated alkene indicates that the N-C bond formation is not reversible after C-Cu homolysis in this reaction.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on these observations we concluded that the reaction most likely proceeds via direct capture of an sp 2 -hybridized carbon radical intermediate with TEMPO 18-21 (Scheme 1). The complete retention of the geometry of the isolated alkene indicates that the N-C bond formation is not reversible after C-Cu homolysis in this reaction.…”
Section: Resultsmentioning
confidence: 94%
“…m.p. 140-145 °C; [α] 21 D = −64.1 °(c = 2.0, CHCl 3 ); 1 H NMR (500 MHz, CDCl 3 ) δ 7.70 (s, 2H), 4.24 (dd, J = 12.5 Hz, 3.0 Hz, 1H), 3.84 (t, J = 8.0 Hz, 1H), 3.67 (s, 3H), 3.63 (m, 1H), 3.12 (AB quartet, J = 10.5 Hz, Δν = 20.6 Hz, 2H), 1.74 (m, 2H), 1.50-1.58 (m, 6H), 1.43 (s, 18H), 1.15 (s, 3H), 1.06 (s, 6H), 1.04 (s, 3H), 0.41 (s, 3H); 13 C NMR (75 MHz, CDCl 3 ) δ 163.2, 144.8, 131.6, 125.9, 79.9, 64.6, 61.5, 59.7, 58.1, 44.5, 39.6, 37.4, 36.0, 33.2, 31.7, 26.4, 25.7, 20.0, 17.1; IR (neat, thin film) ν 2955, 2874, 1471, 1453, 1405, 1349, 1253, 1225, 1165, 1125, 1042, 1008, 967, 920, 885, 812, 757, 710, 632, 595 cm −1 ; HRMS (ESI) calcd for [M+H] + C 31 H 55 O 4 N 2 S 1 : 551.3877, found: 551.3887.…”
Section: Methodsmentioning
confidence: 99%
“…An initial screen of several halogen sources (NBS, CBr 4 , NIS, I 2 , and 2,4,4,6-tetrabromocyclohexa-2,5-dienone) revealed that significant background aminohalogenation occurred under the reaction conditions in the absence of the [Cu( R , R )-Ph-box](OTf) 2 catalyst. Fortunately, however, we did find that 2-iodopropane [14] did not produce any aminoiodination product ( 4a ) under these reaction conditions in the absence of catalyst (Table 1, entry 1). When the reaction was carried out in the presence of the chiral catalyst (20 mol%) under these reaction conditions 2-iodomethylindoline 4a was obtained in 84% yield and with 70% enantiomeric excess (Table 1, entry 2).…”
mentioning
confidence: 99%
“…Second, a nucleophilic alkyl radical 50 arises from the addition step, which is effectively trapped by electrophilic salt 48 to give azo compound 51. As a result of several improvements, the methodology is now applicable for a wide range of polar to non-polar alkenes with almost no restrictions on the substitution pattern of the diazonium salt [101,102]. Moderate diastereoselectivities have been obtained in first attempts with chiral auxiliaries [103].…”
Section: Carboamination Reactionsmentioning
confidence: 94%